Impact of the COVID-19 pandemic on the academic life of higher education students: A rural South African perspective from a global study - Alex, J. K. (South African Journal of Higher Education, 2022)
Globally, the COVID-19 pandemic has become a greatest challenge in all sectors of life in the 21st Century. Due to worldwide lockdown and social distancing regulations, higher education institutions who offer face-to face classes had to go online to provide educational services to their students, which had major impacts on student lives. To study the immediate effects of it, a global study on the life of higher education students, initiated by University of Ljubljana (with international partners) was conducted as a voluntary and anonymous online survey across the world started on 5 May 2020. The survey targeted higher education students ‒ on what student life looks like during the COVID-19 pandemic, in different parts of the world. This article reports on part of that global study, reporting on the teaching and learning aspect of a sample of 274 undergraduate students from a South African rural higher education institution (HEI) who participated in the study. Thus, this article highlights the immediate impacts of the pandemic during 5 May – 15 June 2020 of the rural HEI. The study is important as the student perspective can have an impact on post- COVID academic policies of HEIs with similar contexts.